2012
DOI: 10.1007/s00359-012-0784-4
|View full text |Cite
|
Sign up to set email alerts
|

Time disparity sensitive behavior and its neural substrates of a pulse-type gymnotiform electric fish, Brachyhypopomus gauderio

Abstract: Roles of the time coding electrosensory system in the novelty responses of a pulse-type gymnotiform electric fish, Brachyhypopomus, were examined behaviorally, physiologically, and anatomically. Brachyhypopomus responded with the novelty responses to small changes (100 μs) in time difference between electrosensory stimulus pulses applied to different parts of the body, as long as these pulses were given within a time period of ~500 μs. Physiological recording revealed neurons in the hindbrain and midbrain that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In this readout context, one can postulate that centromedial spherical neurons represent the electric image of objects as a latency pattern, while at the lateral map, instead, spherical cells require synchronized input from multiple afferents from a larger region of the skin and may generate a reference signal that can be used downstream for latency decoding. In fact, all spherical neurons project to the magnocellularis nucleus where a Jeffress-like circuit has been described (pulse fish: Réthelyi and Szabó, 1973b;Sotelo et al, 1975;Matsushita et al, 2013;wave fish: Carr et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In this readout context, one can postulate that centromedial spherical neurons represent the electric image of objects as a latency pattern, while at the lateral map, instead, spherical cells require synchronized input from multiple afferents from a larger region of the skin and may generate a reference signal that can be used downstream for latency decoding. In fact, all spherical neurons project to the magnocellularis nucleus where a Jeffress-like circuit has been described (pulse fish: Réthelyi and Szabó, 1973b;Sotelo et al, 1975;Matsushita et al, 2013;wave fish: Carr et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…This cell phenotype is characteristic of the fast auditory pathways of higher vertebrates, occurring at different processing stages from the cochlear nuclei to the superior coliculi (Bal and Oertel, 2001;Manis and Marx, 1991;Carr, 1993;Koch and Grothe, 2003). They were also reported at the spinal ganglia (Yan et al, 2007) and dorsal horn of mammals (Prescott and De Koninck, 2002) and in the fast electrosensory pathways of gymnotiforms (Nogueira et al, 2006;Matsushita et al, 2012).…”
Section: The Phenotype: the One-spike-onset Neuronsmentioning
confidence: 73%
“…Accordingly, there is also some evidence suggesting this variable association of lowand high-threshold K + currents in spherical neurons of wave-type electric fish (Mehaffey et al, 2006). Interestingly, a recent article showed that spherical neurons of Brachyhypopomus gauderio, a slow electric organ discharge (EOD) rate pulse gymnotiform that shows large differences in sociality with G. omarorum (Silva et al, 2007), do not exhibit the low responsiveness window and the long refractory period observed in G. omarorum (Matsushita et al, 2012). In addition, it is likely that the expression of high threshold conductance in spherical neurons of the wave-type fish Apteronotus and Eigenmannia allows them to follow the relatively high frequencies of their EODs.…”
Section: The Phenotype: the One-spike-onset Neuronsmentioning
confidence: 99%
See 2 more Smart Citations